Grafts containing human amniotic epithelial cells reduce hyperactivity in open-field and digital photo-actometer after Trimethyltin chloride lesion - Omprakash, KV; Muthusamy, R; Devanand, B; Puranik, Nagaraja; Mallikarjun, M (Journal of Institute of Medicine Nepal, 2010)
Introduction: The aim of present study is to provide adequate numbers of cells to appropriate sites for useful cellular replacement to overcome the functional deficits caused by the Trimethyltin chloride lesion. Methods: The effect of Transplanted Human Amniotic Epithelial (HAE) cells in hippocampus after Trimethyltin chloride lesion was tested on Open-field activity and Digital Photoactometer during different time duration. Hippocampal disorder was induced by the intra peritoneal administration of Trimethyltin chloride (TMT) (Sigma chemicals, U.S.A) at a single dose of 7.5 mg/kg body weight or two divided doses of 3.75 mg/kg body weight for two days. Human Amniotic Epithelial cells were isolated from placenta obtained from uncomplicated elective caesarian. Using standard co-ordinates Human Amniotic Epithelial cells were transplanted at four sites of hippocampus. Results: In present study, we observed that the transplanted Human Amniotic Epithelial cells can aid in the partial recovery of hyperactivity induced by the Trimethyltin chloride lesion in Open-field activity and Digital Photoactometer. Conclusions: The present study concludes that the Human Amniotic Epithelial cells may be used as a suitable donor tissue to alleviate various degenerative diseases in animal model before the clinical trial in humans, who are suffering from various degenerative diseases. DOI: http://dx.doi.org/10.3126/joim.v32i1.3998 Journal of Institute of Medicine, April, 2010; 32:1 pp.24-30